Age acquisition norms from elderly Spanish people: characteristics and the prediction of word recognition performance in Alzheimer's disease - Fernando Cuetos (Psicológica, 2012)
Age of acquisition is possibly the single most potent variable affecting lexical access. It is also a variable that determines the retention or loss of words in patients who have suffered brain injury, and in patients with Alzheimer´s disease. But the norms of age of acquisition currently available have largely been obtained from university students whereas the ages of acquisition for some words are very different for young people compared with the elderly. The aim of this study was to develop age of acquisition norms for a sample of 500 words with people over 60 years. When these norms were compared with others from young people in predicting the results of a group of Alzheimer patients in a lexical selection task we found that the elderly ratings made a better prediction of the data. We recommend that for studies using older participants appropriate norms should be used in place of those obtained from young adults.